BIOLOGICAL AGENTS IN MEDICAL THERAPY - Lysenko, N. V.; Kartvelishvili, A. Y. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Presented clinical pharmacology of biological products under the ATC classification system. The classification, characteristics of pharmacodynamics of drugs. An algorithm for the use of biological agents in therapeutic practice: rheumatology, gastroenterology, neurology. Examined in detail the absolute and relative contraindications and side effects of biological agents, as well as control measures in their long-term use.